Role of Teacher Support and Self-Capability in Engagement with Students at MAS Tahfizhil Quran Medan - Tanjung, Yushar; Darma, Aditya; Nasution, Ihsan Syahaf (Education & Learning, 2024)
This research aims to explore the role of teacher support and self-efficacy in influencing student engagement in the Mas Tahfizhil Quran education program. Student engagement is an important factor in the success of tahfizh programs, but the factors that influence it are not yet fully understood. Quantitative research methods were used by collecting data through questionnaires distributed to Mas Tahfizhil Quran students. Data analysis was carried out using descriptive statistical techniques and regression to evaluate the relationship between the variables studied. The results showed that teacher support had a significant influence on student engagement in the tahfizh program, with strong support from teachers tending to increase the level of student engagement. Apart from that, students' self-efficacy is also proven to have a significant impact on the level of engagement, where students with better self-efficacy tend to be more involved in learning activities. This research provides a better understanding of the factors that influence student engagement in the Mas Tahfizhil Quran education program, as well as practical implications for increasing the effectiveness of the program through increasing teacher support and fostering student self-efficacy.